Adipose-Derived Stem Cell–Enriched Lipotransfer Reverses Skin Sclerosis by Suppressing Dermal Inflammation. Issue 3 (28th June 2022) - Jiang, Wenqing; Wang, Jing; Lin, Jiayan; Jiang, Shenglu; Quan, Yuping; Liao, Yunjun; Gao, Jianhua; Cai, Junrong
Abstract : Background: Scleroderma is a chronic autoimmune disease with an incidence of 2.7 per 100, 000 people. Traditional lipotransfer has been used to treat atrophic sclerotic skin. Enzymatically processed cell-assisted lipotransfer and mechanically processed stromal vascular fraction gel are fat products with abundant adipose-derived stem cells. This study assessed whether adipose-derived stem cell–enriched lipotransfer elicits superior therapeutic effects on scleroderma. Methods: Scleroderma was induced in nude mice by injections of bleomycin for 4 weeks. Human-derived Coleman fat, cell-assisted lipotransfer, or stromal vascular fraction gel (0.1 ml) was injected into sclerotic lesions. Histologic examinations, terminal deoxynucleotidyl transferase dUTP nick end labeling, and expression analyses of inflammatory factors in skin lesions and transferred fat were performed at 4 weeks after implantation. Results: Dermal thickness was lower in the groups injected with Coleman fat (339.0 ± 19.66 µm), cell-assisted lipotransfer (271.0 ± 16.15 µm), and stromal vascular fraction gel (197.8 ± 12.99 µm) than in the group injected with phosphate-buffered saline (493.3 ± 28.13 µm) ( p < 0.05). The numbers of terminal deoxynucleotidyl transferase dUTP nick end labeling + and Mac2 + cells in fat tissue were significantly higher in the group injected with Coleman fat than in those injected with stromal vascular fraction gel and cell-assisted lipotransfer. Expression of monocyte chemotactic protein-1 and interleukin-6 was significantly lower in the adipose-derived stem cell–enriched groups than in the Coleman fat group. Histologic analysis showed there were far fewer macrophages and myofibroblasts in skin lesions in the adipose-derived stem cell–enriched groups than in the Coleman fat group. Conclusions: Transplantation of stromal vascular fraction gel and cell-assisted lipotransfer, which contain abundant adipose-derived stem cells, reduces the levels of apoptotic cells and inflammation, significantly reverses skin sclerosis, and elicits superior anti-inflammatory and antifibrotic effects on scleroderma. Clinical Relevance Statement: This study provided an alternative adipose-based therapy, adipose-derived stem cell–enriched fat, for sclerotic lesions and showed its validity for interfering with the inflammation and fibrosis.